2017
DOI: 10.1021/acs.jpcc.7b06107
|View full text |Cite
|
Sign up to set email alerts
|

Long Vertical Distance Bonding of the Hexagonal Boron Nitride Monolayer on the Cu(111) Surface

Abstract: viii Cu(111)-Substrat auf. Stärkere Wechselwirkungen an der Grenzfläche wurden nur dann gefunden, wenn die hBN-Schicht eine höhere Dichte an strukturellen Defekten aufwies. In diesen Fällen konnte die darunter liegende Cu(111)-Oberfläche die azimutale Orientierung der PTCDA-Domänen beeinflussen. Abschließend wurden die optischen Eigenschaften von PTCDA/hBN/Cu(111) gemessen und mit denen von PTCDA/Cu(111), wo die erste PTCDA-Lage die höheren PTCDA-Lagen von der Metalloberfläche entkoppelt, verglichen. Raman-Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 144 publications
(941 reference statements)
7
23
0
Order By: Relevance
“…In particular, we found that hBN on Cu(111) forms a flat layer at a relatively large vertical distance from the Cu(111) top layer of 3.24 Å using an X-ray standing-waves analysis [30]. This large distance is, in principle, in agreement with the results reported independently by Schwarz and co-workers [31].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, we found that hBN on Cu(111) forms a flat layer at a relatively large vertical distance from the Cu(111) top layer of 3.24 Å using an X-ray standing-waves analysis [30]. This large distance is, in principle, in agreement with the results reported independently by Schwarz and co-workers [31].…”
Section: Introductionsupporting
confidence: 91%
“…The structural quality of the bare Cu(111) surface, the hBN layers, and the PTCDA layers was checked by LEED. We used a SPA-LEED instrument as described in [30]. An additional annealing step between the last sputter cycle and the borazine deposition was omitted here in order to prevent segregation of chemical impurities from the Cu bulk to the surface, which we otherwise occasionally observed as additional LEED spots.…”
Section: Methodsmentioning
confidence: 99%
“…If this displacement is impossible, for instance due to the dimensionality of the adsorbate, then Pauli repulsion has the capacity to suppress chemical interactions between adsorbate and substrate. The interaction model developed here for the case of graphenelike planar adsorbates appears to be applicable to other 2D materials 075410-5 [54] as well and is therefore of a more general nature. It thus offers important insights into the interaction mechanisms at metal surfaces, in particular the balance between repulsive and attractive interactions.…”
Section: Discussionmentioning
confidence: 99%
“…is a free parameter that reflects the fact that XSW is only sensitive to the vertical position with respect to H modulo the period of the standing wave field. Importantly, several effects sensitively influence f H [30,[33][34][35] and effects beyond the current theoretical description are indicated by observed f H variations between different chemical elements [33] and chemical species of the same element [34]. P H is a much more robust observable.…”
mentioning
confidence: 81%